Competing with the New York Stock Exchange* - Brown, William O.; Mulherin, J. Harold; Weidenmier, Marc D. (Quarterly Journal of Economics, 2008)
Research on information economics and securities markets dating back to Stigler (Journal of Political Economy, 69 (1961), 213–225; Journal of Business, 37 (1964), 117–142) argues that trading will tend to centralize in major market centers such as the New York Stock Exchange (NYSE). The NYSE's recent mergers with Archipelago and Euronext bring questions about the viability and effects of competition between stock exchanges to the policy forefront. We examine the largely forgotten but unparalleled episode of competition between the NYSE and the Consolidated Stock Exchange of New York (Consolidated) from 1885 to 1926. The Consolidated averaged 23% of NYSE volume for approximately forty years by operating a second market for the most liquid securities that traded on the Big Board. Our results suggest that NYSE bid-ask spreads fell by more than 10% when the Consolidated began to trade NYSE stocks and subsequently increased when the Consolidated ceased operations. The empirical analysis suggests that this historical episode of stock market competition improved consumer welfare by an amount equivalent to US$9.6 billion today.